Homogenization of long-term GPS monitoring series at permanent stations in Central Europe and Balkan Peninsula - HEFTY, Ján; IGONDOVÁ, Miroslava; DROŠČÁK, Branislav (Contributions to Geophysics and Geodesy, 2009)
The network of 54 permanent GPS stations situated in Central Europe, Alpine-Adriatic region and Balkan Peninsula is analyzed by uniﬁed processing strategy, using homogeneous models for reduction of physical eﬀects, and is uniformly referred to as the International Terrestrial Reference Frame – ITRF2005. The resulting time series of observed site coordinates and site troposphere parameters from interval 1999.5 to 2008.5 are inspected for their continuity, homogeneity, long-term drift, and seasonal variations.